2016
DOI: 10.1186/s12711-016-0230-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and genomic basis of antibody response to porcine reproductive and respiratory syndrome (PRRS) in gilts and sows

Abstract: BackgroundOur recent research showed that antibody response to porcine reproductive and respiratory syndrome (PRRS), measured as sample-to-positive (S/P) ratio, is highly heritable and has a high genetic correlation with reproductive performance during a PRRS outbreak. Two major quantitative trait loci (QTL) on Sus scrofa chromosome 7 (SSC7; QTLMHC and QTL130) accounted for ~40 % of the genetic variance for S/P. Objectives of this study were to estimate genetic parameters for PRRS S/P in gilts during acclimati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
65
8
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(83 citation statements)
references
References 26 publications
8
65
8
2
Order By: Relevance
“…This is important to avoid bias in the marker estimates. These results are in accordance with other studies that estimated marker effects using all markers and then predicted breeding values based on QTL SNPs only [67,68]. Therefore, these results indicate that genomic prediction for VS traits is possible in purebred pigs.…”
Section: Genomic Predictionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is important to avoid bias in the marker estimates. These results are in accordance with other studies that estimated marker effects using all markers and then predicted breeding values based on QTL SNPs only [67,68]. Therefore, these results indicate that genomic prediction for VS traits is possible in purebred pigs.…”
Section: Genomic Predictionsupporting
confidence: 91%
“…Finally, GPAs were calculated using SNP estimates and genotypes from markers outside these QTL and referred to as REST. For REST, SNPs within 3 Mb from the limits of the QTL were removed to avoid SNPs in some degree of LD with the QTL to capture any unwanted effects [67].…”
Section: Genomic Predictionmentioning
confidence: 99%
“…This proposition is further strengthened by results from an outbreak in a reproductive sow herd reported by Serão et al (2014), which found high favorable genetic correlations of S:P ratio measured by ELISA ∼46 days after the outbreak with reproductive performance (litter size, number stillborn, number mummies) during the outbreak. Indeed, further studies indicated moderate genomic prediction accuracies for PRRS S:P ratio using SNPs located within two genomic regions on SSC7 that had large effects on S:P ratio, while the rest of the genome showed limited predictive ability (Serão et al, 2016). Further work is needed to confirm these associations, as well as the relationship of S:P ratio following vaccination with host response and performance during PRRS infection.…”
Section: Antibody Responsementioning
confidence: 98%
“…For the next step, pigs differing at most in susceptibility/resistance were used in experiments to take a detailed look at their genetic peculiarities. Three major setups were applied initially: QTL analysis [39] and genome-wide association study (GWAS) were used to identify chromosomal areas and eventually single nucleotide polymorphisms (SNPs) associated with PRRS phenotypes (e.g., degree of viremia, lung lesions and performance after PRRSV infection [13][14][15], antibody response [105]) and differential expression experiments to detect genes via differences in their expression levels in susceptible and resistant pigs [103,104]. The most significant results have been achieved by Joan Lunney (USDA), Bob Rowland (Kansas State University) and colleagues, particularly in the context of the PRRS Host Genetics Consortium (PHGC, for a review, see [69]).…”
Section: Natural Genetic Disease Resistance Against Prrs In Swine Brementioning
confidence: 99%